2021
DOI: 10.1016/j.ajur.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Urine microscopy and neutrophil–lymphocyte ratio are early predictors of acute kidney injury in patients with urinary tract infection

Abstract: Objective Urinary tract infection (UTI) is a common cause of morbidity and hospitalisation in the population worldwide. Upper UTI is indolent and causes subclinical acute kidney injury (AKI) resulting in preventable cause of scarring of renal parenchyma. We explored urinary and serum levels of kidney injury molecule-1 (KIM-1), haematological parameters and quantitative urine microscopy parameters to predict kidney injury. Methods Neutrophil–lymphocyte ratio (NLR) is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…In addition, this score was found to be significantly useful in identifying the need for as well as for the duration of hospitalization (p < 0.000). These findings were similar to that of Perazella et al, 17 and Kana et al 16 None of the virulence factors were associated with the presence of AKI nor was there any association with the need for hospitalization or duration of admission. Our findings did not correlate with that of Wang et al 18 We found the association of virulence factors of UPEC with non-secretors (p < 0.000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, this score was found to be significantly useful in identifying the need for as well as for the duration of hospitalization (p < 0.000). These findings were similar to that of Perazella et al, 17 and Kana et al 16 None of the virulence factors were associated with the presence of AKI nor was there any association with the need for hospitalization or duration of admission. Our findings did not correlate with that of Wang et al 18 We found the association of virulence factors of UPEC with non-secretors (p < 0.000).…”
Section: Discussionsupporting
confidence: 91%
“…These values are similar to the findings in our previous study. 16 NLR is associated with a range of diseases from exogenous steroid administration to cancer and this is a major limitation in its utility as a diagnostic or prognostic tool. Our patients did not UM score >2 was found to be significantly useful in the identification of AKI at presentation as well as in the extrapolation to predict AKI during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…21 Semi-quantitative urine microscopy has been studied by other authors from different geographic settings to assess AKI and our study results are similar in detection and prediction of persistence of AKI in the first two weeks. 68 In our study, we did not study the single nucleotide polymorphisms (SNPs) associated with blood group secretor status, as studied by many of the recent studies due to the possibility of variations in the SNPs in different populations. However, this is a limitation in our study as we have studied only the phenotypic expression of blood group antigens in saliva and this needs to be explored further to understand the pathogenesis of increased risk for AMR among non-secretors.…”
Section: Discussionmentioning
confidence: 99%
“…Urine KIM-1 of rats was increased after two days of E. coli injection and showed sensitivity in the diagnosis of febrile urinary tract infection in children (44). Serum and urine KIM-1 was low and couldn't be diagnosed for AKI in adults with urinary tract infections (46). Urine KIM-1 is a marker for ischemic kidney injury but is not good for screening AKI development in children having urinary tract infections (45).…”
Section: Kim-1 In Urinary Tract Infectionmentioning
confidence: 99%